Nova-Bollinger Ni-Cu sulfide ore deposits, Fraser Zone, Western Australia: Petrology of the host intrusions sulfide-silicate textures and emplacement mechanisms of the ores. Issue 1 (1st December 2019) - Taranovic, Valentina; Stephen, J. Barnes; Beresford, Steve; Miller, John; Rennick, Steven
Summary: The Nova-Bollinger Ni-Cu sulfide ore deposits are hosted within a suite of mafic-ultramafic intrusive cumulate bodies. The Lower Intrusion is a thin semi-conformable chonolith comprising unlayered mafic to ultramafic orthocumulates, hosting the bulk of the mineralisation. The much thicker overlying Upper Intrusion is bowl-shaped and modally layered with alternating peridotite and norite mesocumulate layers. A distinctive rock-type containing both orthopyroxene and olivine as cumulus phases is a characteristic of the Lower Intrusion. The intrusions differ in olivine and spinel chemistry, and in the volume of sulfides. Sector zoning in Cr content of pyroxenes is observed in the Lower Intrusion, and in the lower marginal zone of the Upper, and is attributed to crystallisation under supercooled conditions. Symplectite orthopyroxene-spinel-amphibole coronas at olivine-plagioclase contacts are attributed to near-solidus peritectic reaction between olivine, plagioclase and liquid during high pressure emplacement (>6 Kb), consistent with high Al contents in igneous pyroxenes and estimates of the peak regional metamorphism. The Upper and Lower Intrusion rocks represent cumulates from a similar parental magma, derived via multiple magma pulses, variably fractionated and undergoing sulfide saturation prior to emplacement into the deep crust at pressures of 6-10 Kb during the peak of regional metamorphism under extremely low cooling rates. The ores show a remarkable assemblage of textures indicative of emplacement into hot, soft country rocks at a large-scale melting-infiltration front. Sulfide infiltration was accompanied by partial melting of the country rock producing felsic leucosomes, some of them strongly enriched in garnet, showing close spatial association with sulfide infiltrations and veins. Coarse grained pentlandite – chalcopyrite – pyrrhotite "loop textures" are characteristic of all ore types, down to the scale of the infiltrating sulfides within the gneisses, and are regarded to be diagnostically magmatic textures generated by sulfide liquid fractionation and growth of high-T pentlandite by peritectic reaction between fractionated sulfide melt and early crystallised MSS.